Voices of Labor : Creativity, Craft, and Conflict in Global Hollywood - Sanson, Kevin; Curtin, Michael (Book collections on Project MUSE., 2017)
"The film industry in Hollywood now employs a global mode of production run by massive media conglomerates that mobilize hundreds, sometimes thousands, of workers for each feature film or television series. Yet these workers and their labor remain largely invisible to the general audience. In fact, this has been a signal characteristic of Hollywood style for more than a hundred years: everything that matters happens onscreen, not off. Consequently, when it comes to movies and television, the voices heard most often are those belonging to talent and corporate executives. Those we hear least are the voices of labor, and it's that silence we aim to redress in the collection of interviews in this book. Drawing from the detailed and personal accounts in this collection, we offer three interrelated propositions about the current state and future prospects of craftwork and screen media labor: 1. Craftwork exists within an intricate and intimate matrix of social relations. 2. Hollywood craftwork today constitutes a regime of excessive labor. 3. Screen media production is a protean entity. We organized the collection into three sections: company town, global machine, and fringe city. The first section refers to Hollywood's historic roots as a core component of the motion picture business. The second section engages more directly with the spatial dynamics of film and television production to underscore the economic and political structures that are integrating distant locations into the studios' mode of production. We close with a section on the visual effects sector, in which stories shared by vfx artists, advocates, and organizers specifically illustrate how the industry today relies on marginal institutions to sustain its power and profitability"--Provided by publisher